The birthday girl - Leather, Stephen author (London : Coronet Books, 1996)
Mersiha has been adopted from war-torn Yugoslavia, and has grown up to be an all-American teenager. When she discovers that her adoptive father is in financial difficulties she decides to intervene, but the consequences of her interference are lethal.
Keywords: Conspiracy -- Fiction; Thrillers (Fiction)